Angiotensin IV is induced in experimental autoimmune encephalomyelitis but fails to influence the disease - Manzel, Arndt; Domenig, Oliver; Ambrosius, Bjoern; Kovacs, Agnes; Stegbauer, Johannes; Poglitsch, Marko; Mueller, Dominik N.; Gold, Ralf; Linker, Ralf (Journal of Neuroimmune Pharmacology, 2014)
In multiple sclerosis (MS) and its corresponding animal models, over-activity of the renin-angiotensin system (RAS) has been reported and pharmacological RAS blockade exerts beneficial effects. The RAS generates a number of bioactive angiotensins, thereby primarily regulating the body's sodium homeostasis and blood pressure. In this regard, angiotensin IV (AngIV), a metabolite of the RAS has been shown to modulate inflammatory responses. Here we studied potential implications of AngIV signalling in myelin oligodendrocyte glycoprotein (MOG) peptide induced murine experimental autoimmune encephalomyelitis (EAE), a close-to-MS animal model. Mass spectrometry revealed elevated plasma levels of AngIV in EAE. Expression of cognate AT4 receptors was detected in macrophages and T cells as major drivers of pathology in EAE. Yet, AngIV did not modulate macrophage or T cell functions in vitro or displayed detectable effects on neuroantigen specific immune responses in vivo. The data argue against a major contribution of AngIV signalling in the immunopathogenesis of MOG-EAE.
EVALuna2:22281